Avaliação dos impactos das variáveis ambientais na qualidade da prestação do serviço de distribuição de energia elétrica no Brasil - AZEVEDO, Luísa Morais (2024)
Climate change has been increasingly noticeable through the extreme weather events experienced in recent years around the world. This scenario is no different in Brazil, which registered an increase in the average temperature of 1,52 ° C between the years of 1850 and 2019. As a consequence of these changes increasingly relevant and more frequent climate events are being recorded, such as those that occurred in the second half of 2023 in São Paulo and Rio Grande do Sul. That said, it’s substantial to evaluate the impacts of these events in the critical infrastructure sectors, in particular, in the energy distribution. Therefore, the calculation of correlation coefficients was chosen to demonstrate the impact of the climate variables, related to temperature, rainfall and wind speed, on the operational energy distribution quality indicators, considering the total and the values after purges provided for in the regulations. The years 2013, 2018 e 2023 were evaluated, encompassing around 3 thousand electrical sets according to geospatial configurations on December 31, 2020. Interpolation methods, exploratory analysis and removal of outliers were used to process the data. Lastly, the inferential statistical analysis was performed, in which the Pearson and Spearman correlation coefficients were obtained, and the significance test. From the results, it was observed a adequate level of significance, in other words, it is possible to infer the population coefficients from the observed sample. From the qualitative analysis of the correlation coefficients, the indicator of the total Equivalent Duration of Interruption per Consumer (total DEC) is the most affected by climatic conditions, mainly related to precipitation, average temperature and maximum wind gust, having presented a moderate correlation. Another conclusion is that, given the correlation coefficients for total and collective continuity indicators, being lower for the latter, the purges provided for in current regulations are reasonably in line with their purpose. Finally, with the results achieved, it is expected to support energy distributors in the search for triggers of climatic variables for better allocation and dispatch of teams, with the aim of reducing the duration of interruptions in adverse weather situations.